THE COMPARATIVE ANALYSIS OF THE POPULATION MEDICAL EXPOSURE IN RUSSIAN FEDERATION AND TATARSTAN REPUBLIC FOR THE PERIOD 2002-2006 - V. G. Morozov; R. K. Ismagilov; A. M. Mousin (Радиационная гигиена, 2017)
The conducted comparative analysis of the medical exposure of the population of Russian Federation and one of its administrative territories reveals the leading importance for the medical exposure reduction of the renewing of X-ray equipment and the methods of the patient dose determining and the regulation of X-ray investigations. The introduction of the instrumental control methods predetermines comparatively low doses from medical exposure for the population of the Tatarstan Republic.